The effect of information quality on trust mediated by social psychological distance and its effect on purchase intention - Hidayah, Rahmat; Thabrani, Gesit (Marketing Management Studies, 2024)
This study purpose to analyze the influence of information quality and trust mediated by social psychological distance on purchase intentions of Tik Tok users in Padang City. The population in this study is all the people of Padang City who know about online shopping features through the Tiktok application. This study involved 144 respondents as a sample. Data collection was carried out by distributing online questionnaires, and data was processed using SmartPLS software. The findings of this study indicate that (1) the quality of information has a positive and significant effect on trust, (2) the quality of information has a positive and significant effect on social psychological distance, (3) social psychological distance has a positive and significant effect on trust. (4) The quality of information has a positive and significant effect on trust with social psychological distance as mediation, (5) trust has a positive and significant effect on purchase intentions.